Less sugar advertising campaign / Wan Ruzni Elliza Wan Mohd Zin - Wan Mohd Zin, Wan Ruzni Elliza (Faculty of Art and Design, 2013)
The purpose of this study is to analyze and find out about the effectiveness of advertising media to Less Sugar Campaign. Less Sugar Campaign was established in 2010. The purpose of this campaign is held to remind people of Malaysia about its dangers of excessive sugar consumption and would be detrimental to health. After a two year campaign to be held, it seemed to disappear and no progress on this campaign. In fact more and more people in Malaysia suffering from obesity due to excessive sugar consumption. It is likely that the campaign was held not successful and the people of Malaysia are unable to realize the dangers of excessive sugar consumption. Ad campaign in the post may not be placed in strategic places and many are not aware of the existence of this campaign. Advertising media should play an important role for enlightening and profound impact on the campaign. In this paper, researchers have conducted a study on effective advertising media for the success of a campaign. 38 respondents had completed questionnaires on Less Sugar Campaign and also effective advertising media for their opinions to the success of a campaign. Their answers were documented and will be presented in this academic writing